Monoclonal antibody production: viability improvement of RC1 hybridoma cell in different types of bioreactor - Mel, Maizirwan; Abdul Rahman, Abdul Rafiz; Mohamed Salleh, Mohamad Ramlan; Hashim, Yumi Zuhanis Has-Yun (Springer, 2008)
The study was done to improve the viability of the RC1 hybridoma cell in order to produce more amount of monoclonal antibody (mAb). By using the optimized media, the cell had been cultured in two bioreactor systems which were the MiniPerm and Stirred Tank bioreactor (ST bioreactor), and the results were compared to the one obtained by using the T-Flask bioreactor which was used as a standard. The results showed that the ST bioreactor was able to improve the viability of the cell to the value of 91.8% which was a little bit better than the one obtained by the MiniPerm bioreactor (88.6%) and far better than that of achieved by the T-Flask bioreactor (76.4%). This was well correlated with the good growth performance of the cell in the ST bioreactor with the specific growth rate (l) value of 0.0289 h-1 followed by MiniPerm bioreactor with the value of 0.0243 h-1 and then the T-Flask with the value of 0.0151 h-1. The low value of doubling time (td) obtained in the ST bioreactor (24 h) compared to the one obtained in the MiniPerm (29 h) and T-Flask bioreactor (46 h) had also contributed to the higher value of cell viability. As a result a higher concentration of mAb was able to be produced by the ST bioreactor (0.42 g l-1) compared to that of the MiniPerm (0.37 g l-1) and T-Flask bioreactor (0.23 g l-1).